Repetitive low energy impacts on alpine ski helmets - Swaren, M.; Holmberg, H. C.; Eriksson, A. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Alpine ski races often aim to follow as short a line as possible which causes the skiers to hit the gates with arms, shoulders, boots and helmets when moving the gates out of the path of travel. In giant slalom, the helmets are particularly exposed to violence caused by the skier hitting the gates, due to the trajectory of the skier relative to the gates. These multiple impacts can cause damage to the helmet`s core. The purpose of this study was thus to develop a method for investigating how alpine ski helmets perform when exposed to repeated low impact violence, similar to the impacts caused by a gate when hit by an alpine skier